Fly, butterfly, fly! - Rau, Dana Meachen, 1971- (New York : Marshall Cavendish Benchmark, 2008)
"Describes characteristics and behaviors of butterflies"--Provided by publisher.
Includes index.
Keywords: Butterflies -- Juvenile literature